VARIASI BENTUK WAJAH LAKI-LAKI DAN PEREMPUAN DARI DESA PANGLIPURAN, KABUPATEN BANGLI, PROVINSI BALI - PUTRA, AGUNG EKO CAHYA KUSUMA; WIRASITI, NI NYOMAN; SETYAWATI, IRIANI (Jurnal Biologi Udayana; Vol 21 No 2 (2017): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2017.vol21.i02.p03, 2017)
This research determined male and female face type of the adults in Panglipuran adults. The analysis of face types Geometric Morphometric Technique in thin-plate-splin (tps) program. Adults female and 14 male aged 25-35 years old were photographed for both frontal and lateral faces with a digital camera Canon EOS 60D. Landmark data was processed by photo processor program tpsDig version 2.04, tpsSuper version 1.13, tpsRelw version 1.42, tpsSplin 1.20 and both of ape and gee package of R Program version 3.2.5. The average of male’s face shape type in Panglipuran village was ellipse and round for female’s. We found 2 frontal and 2 lateral for male’s face variation, we also found 3 frontal and 3 lateral for female’s. Frontal face of male and female that showed high variation included right subaurale, left subaurale, right gonion, left gonion, and gnathion. Lateral face of male and female that showed high variation were trichion, frontozygomaticus, superciliare, superaurale, pogonion, glabella, the minimum point of the curve below earlobe, gonion and gnathion.